Analisis Kepuasan Mahasiswa UIN SMH Banten Terhadap Penggunaan Bank Tabungan Negara (BTN) Dan Bank Syariah Indonesia (BSI) (Studi Pada Mahasiswa UIN SMH Banten Tahun 2023) - Wahyu Hidayat; Rizki Khoirunnisa; Faridatul Aini; Rizki Azi Prasetia; Henny Saraswati (Universitas 45 Surabaya, 2023)
This study aims to analyze the satisfaction of UIN Sultan Maulana Hasanuddin Banten students with the use of Bank Tabungan Negara (BTN) and Bank Syariah Indonesia (BSI). This study used the ndust method by taking samples as many Students who use banking services at both banks. The data were analyzed using descriptive and t-test difference test. The results showed that the majority of students who were respondents preferred to use banking services at Bank Syariah Indonesia (BSI) rather than at Bank Tabungan Negara (BTN). The main reason stated is because Bank Syariah Indonesia (BSI) provides better services and is more in accordance with sharia principles. Overall, the level of student satisfaction with the use of banking services at Bank Syariah Indonesia (BSI) is higher than at Bank Tabungan Negara (BTN). However, the results of the t-test difference test showed that there was no significant difference between the satisfaction of students who used banking services at the two banks. This research provides useful information for both banks to improve services and increase customer satisfaction, especially among students. In addition, this research can also be a reference for future research on customer satisfaction in the banking industry.